Flow-Pattern characterization of biphasic electrochemical cells by magnetic resonance imaging under forced hydrodynamic conditions - Serial, María Raquel (2017)
The fluid dynamics of a liquid|liquid system inside a four-electrode electrochemical cell were studied by velocimetry magnetic resonance imaging (MRI) and flow propagator measurements. To characterize this system fully, three different cell configurations operating at two rotational frequencies were analyzed. Quantitative information about the stability of the liquid|liquid interface and the dynamics of the organic phase were determined. The NMR spectroscopy results were in agreement with the electrochemical measurements performed by using the same experimental setup.